A Fast Multilevel SVPWM Method Based on the Imaginary Coordinate With Direct Control of Redundant Vectors or Zero Sequence Components - Xibo Yuan; Yue Gao; Yongdong Li (IEEE Open Journal of the Industrial Electronics Society, 2020)
This paper for the first time comprehensively presents a multilevel space vector pulse width modulation (SVPWM) method based on the imaginary coordinate system. This method is probably one of the most efficient methods in fast multilevel SVPWMs. It avoids trigonometric operation, look-up tables and only requires simple logic judgement and arithmetic calculation. A distinct advantage of this method over other coordinate-transformation-based methods is that it does not need to transform from the imaginary coordinate system back to the a-b-c (or α-β) coordinate in order to select the redundant vectors using look-up tables. The redundant vectors or zero-sequence components are directly worked out in the proposed method, e.g., for balancing dc-link capacitor voltages, which avoids identifying the starting vector, vector rotation direction (clockwise or anti-clockwise), vector sequence, etc. as used in conventional methods. This paper entails each step to implement this SVPWM method, which can be replicated for multilevel converters with any number of voltage levels. The presented method has been used and validated by various converters, including a three-level and a five-level neutral-point-clamped converter. The archive value of this paper is that it demonstrates a milestone of fast multilevel SVPWM based on coordinate transformation.